2021
DOI: 10.1007/s11205-021-02855-9
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for Sanitation Quality in Low-Income Urban Settlements: Evidence from Kenya, Ghana, and Bangladesh

Abstract: In recent years, shared facilities have contributed substantially to increased access to sanitation in urban areas. While shared sanitation is often the only viable option in densely-populated, low-income urban areas, it is currently considered a “limited" solution by the international community. In this paper, we analyze the conditions under which shared sanitation could be considered of adequate quality and propose a set of indicators associated with sanitation quality to be included in national household su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, the majority of venues assessed in our study were bars (with and without lodging), which is in keeping with the national key population hotspot estimation exercise, where they comprised 75% of hotspots; streets/alleys/highways accounted for 5%, guest house/lodging 4.4%, and brothels (1.6%). Another strength of our study was the use of direct observation, as self-reported measures of sanitation have been shown to have low reliability ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of venues assessed in our study were bars (with and without lodging), which is in keeping with the national key population hotspot estimation exercise, where they comprised 75% of hotspots; streets/alleys/highways accounted for 5%, guest house/lodging 4.4%, and brothels (1.6%). Another strength of our study was the use of direct observation, as self-reported measures of sanitation have been shown to have low reliability ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Settlements in urban areas are generally dense, so there is not enough land to provide standard environmental roads [20], the characteristics of residential buildings in Kampung Braga have high density, the distance of the buildings is close to each other and only separated by roads with a width of 0.5 m -1 m [21]. According to the Regulation of the State Minister for Public Housing of the Republic of Indonesia Number 25 of 2011 about the Implementation of Low-Cost Housing, environmental roads for pedestrians or two-wheeled motorized vehicles are at least 2-3.5 meters wide for the road body, 0.5 -0.75 meters for the road shoulder and has a road benefit area (damaja) between 360 -450 cm [22].…”
Section: Residential Environment Characteristicsmentioning
confidence: 99%
“…Based on observations made in Kenya and Ghana, toilets shared by up to 3 households could be included in the basic service level. According to Meili et al [72] toilets shared among 2-3 households in Kenya and Ghana show good quality. On the other hand, the Sanitation Task Team's recommendation of a sharing limit of no more than five families or no more than 30 people [73] may also be considered even though their proposed maximum number of users is too high.…”
Section: Setting a Benchmark For Inclusion Of 'Quality' Shared Sanita...mentioning
confidence: 99%